Recent progress in organic field‐effect transistor‐based chem/bio‐sensors. Issue 1 (31st January 2022) - Luo, Liang; Liu, Zitong
Abstract: Recent decades have witnessed the huge successes of organic field‐effect transistors (OFETs) and their applications. Among them, OFET‐based sensors have shown promising applications in the field of food safety, industrial security, environmental, and health monitoring. This is due to their advantages in solution processability, flexibility, light weight, and variety in molecular design. This review highlights recent progress in OFET‐based chemical and biological sensors in gas and liquid phase, especially for the past 5 years. The analytes range from small molecules to large biomolecules. The optimizations of OFET devices for sensors, including the semiconducting layers, dielectric layers, electrodes, and their interfaces etc., are illustrated. And their relationships with sensing parameters (sensitivity, selectivity, and response time) as well as the sensing mechanisms are given. Finally, the remaining challenges are discussed. We expect that this review can offer inspiration for future design of OFET‐based sensors. Abstract : OFET‐based sensors have shown promising applications in the field of food safety, industrial security, environmental, and health monitoring. This review highlights recent progress in OFET‐based chemical and biological sensors in gas and liquid phase, especially for the past 5 years.